Degradasi substrat volatile solid pada produksi biogas dari limbah pembuatan tahu dan kotoran sapi - Budi Nining Widarti; Siti Syamsiah; Panut Mulyono (Jurnal Rekayasa Proses, 2012)
Waste from tofu production and cow dung are potential organic materials for biogas production based on the content of volatile solid. This study aims to determine the optimal content of volatile solid in a mixture of tofu production waste-cow dung and to obtain the kinetic parameters of the degradation of volatile solid to form biogas. A mixture at certain composition is put into digester. To obtain anaerobic condition, N2 gas is flown into the digester, and then the digester is sealed. The mixture is incubated in a water bath at a temperature of 35oC for 56 days. Biogas volume and pH are measured every day. Methane, volatile fatty acids and volatile solid are analyzed every 7 days. Carbohydrates, proteins and fats in the slurry are analyzed three times during the production of biogas. The results showed that digester with 12% volatile solid produces the highest biogas yield of 89.522 mL/g volatile solid, with the highest methane concentration 14.68%. Kinetics model of degradation of volatile solid can be approached by a first order reaction model.